2016
DOI: 10.1093/femspd/ftw113
|View full text |Cite
|
Sign up to set email alerts
|

Hfq and three Hfq-dependent small regulatory RNAs—MgrR, RyhB and McaS—coregulate the locus of enterocyte effacement in enteropathogenicEscherichia coli

Abstract: Enteropathogenic Escherichia coli (EPEC) is a significant cause of infantile diarrhea and death in developing countries. The pathogenicity island locus of enterocyte effacement (LEE) is essential for EPEC to cause diarrhea. Besides EPEC, the LEE is also present in other gastrointestinal pathogens, most notably enterohemorrhagic E. coli (EHEC). Whereas transcriptional control of the LEE has been meticulously examined, posttranscriptional regulation, including the role of Hfq-dependent small RNAs, remains underc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 90 publications
3
26
0
Order By: Relevance
“…Beta-galactosidase assays on the translational fusion ( P araBAD -tnaA’-‘lacZ ) containing reporter strains were performed as described in our previous paper [ 19 ], with the exception that bacteria were grown to an optical density of 1.1–1.4 in LB supplemented with ampicillin, arabinose, and IPTG. The same conditions, as described above, were employed for the transcriptional fusion ( P LEE1 -LEE1’-lacZ + ) containing reporter strains with the omission of arabinose from the medium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beta-galactosidase assays on the translational fusion ( P araBAD -tnaA’-‘lacZ ) containing reporter strains were performed as described in our previous paper [ 19 ], with the exception that bacteria were grown to an optical density of 1.1–1.4 in LB supplemented with ampicillin, arabinose, and IPTG. The same conditions, as described above, were employed for the transcriptional fusion ( P LEE1 -LEE1’-lacZ + ) containing reporter strains with the omission of arabinose from the medium.…”
Section: Methodsmentioning
confidence: 99%
“…The T3SS bridges the bacterium to the host cell and facilitates the smuggling of effector proteins into the host where they subvert host signaling pathways to initiate A/E lesion formation [ 4 , 13 , 18 ]. The importance of this genomic island to the bacterium is illustrated by the characterization of over 40 regulatory factors that control the LEE [ 4 , 19 ]. Most regulators target one of the two key regulatory operons— grlRA ( LEE7 ) and/or LEE1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the authors extensively characterized the involvement of Hfq in expression of LEE4 (detailed below), no data describing the specific mechanism of Hfq-dependent regulation of Ler or GrlA expression were reported in that study. However, the Hfqdependent sRNAs MgrR and RyhB directly influence LEE expression in enteropathogenic E. coli (112). These sRNAs were identified following a screen that assessed the impact of core sRNAs on the activity of grlR=-=lacZ reporter fusions.…”
Section: Specific Mechanisms Of Virulence Factor Regulationmentioning
confidence: 99%
“…These sRNAs were identified following a screen that assessed the impact of core sRNAs on the activity of grlR=-=lacZ reporter fusions. Further characterization demonstrated that MgrR base pairs to the 5= UTR of grlR to repress grlR expression and to activate expression of grlA and the LEE, whereas RyhB binds to the grlRA mRNA to repress translation (112) (Fig. 6B).…”
Section: Specific Mechanisms Of Virulence Factor Regulationmentioning
confidence: 99%